Lost in the valley of death : a story of obsession and danger in the Himalayas - Rustad, Harley (Harper, an imprint of HarperCollinsPublishers, 2022)
Chronicles the events leading up to the 2016 disappearance of Justin Alexander Shetler, an adventure traveler who embarked on a "spiritual journey" to the Parvati Valley, a remote and sometimes dangerous area of the Indian Himalayas, from which he never returned.